SOCIAL AND LEGAL BASIS FOR ENSURING EMPLOYMENT OF THE POPULATION IN THE CONDITIONS OF MODERNIZATION OF UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
This article talks about the right of every person to work, the concept of ensuring employment of the population and the responsible body that promotes employment of the population, as well as state guarantees of employment. The article also examines the experience of developed countries in providing employment to the population, highlighting the factors causing unemployment. The level of employment and unemployment of the population in modernizing Uzbekistan, trends in their changes and employment of the population by industry are analyzed. The article develops proposals to ensure employment of the population and reduce unemployment.